MeHg exposure impairs both the catecholaminergic and cholinergic systems resulting in motor and non-motor behavioral changes in Drosophila melanogaster. (25th September 2022) - Bianchini, Matheus C.; Soares, Luiz F.W.; Sousa, João M.F. M.; Ramborger, Bruna P.; Gayer, Mateus C.; Bridi, Jessika C.; Roehrs, Rafael; Pinton, Simone; Aschner, Michael; Ávila, Daiana S.; Puntel, Robson L.
Abstract: Human exposure to the natural environmental contaminant methylmercury (MeHg) has been associated to adverse health effects. Importantly, the mechanisms by which this organomercurial exerts its neurotoxicity have yet to be fully clarified. Therefore, the aim of this study was to evaluate whether exposure to MeHg alters dopamine (DA) and octopamine (OA) levels, acetylcholinesterase (AChE) activity and impacts both motor and non-motor behaviours. We studied the effect of MeHg by feeding 1–2 d old flies (male and females) with 25 and 50 μM MeHg for 4 d and determined effects on survival, motor and non-motor behaviours, oxidative stress, AChE and tyrosine hydroxylase (TH) activities, as well as DA and OA levels. We found that Drosophila melanogaster (D. melanogaster) exposed to MeHg showed a reduction in survival rate, associated with the inhibition of AChE and TH activities in head of flies and decreased DA and OA levels. These changes were accompanied by behavioural alterations, such as locomotor deficit and increased grooming behaviour, in addition to an increase in oxidative stress markers both in head and in body of flies, and an increase in glutathione-S-transferase (GST) activity in head of flies. Collectively, our data support the hypothesis that MeHg neurotoxicity is associated with altered OA and DA levels, AChE inhibition, which may serve, at least in part, as the underpinnings of both motor and non-motor behavioural changes. Highlights: MeHg is a contaminant whose toxic mechanism remains to be better clarified. Here, MeHg exposure decrease in flies' survival and increase in oxidative stress parameters. MeHg also inhibited acetylcholinesterase and Tyrosine Hydroxylase activities. Consequently, dopamine and octopamine levels were lower in MeHg-exposed flies. As a result, impairment in different behaviors was associated to MeHg-exposure.